On the microstructural characteristics of non-equilibrium gamma-precipitates in Cu-Zn-Al alloys - Lovey, Francisco Carlos; Cesari, E. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Lovey, Francisco Carlos. Comisión Nacional de Energía Atómica; Argentina